Gut microbiota on cardiovascular diseases-a mini review on current evidence - Zhang, Shouhong; Li, Jing; Li, Liping; Yuan, Xingxing (Frontiers in Microbiology, 2025)
The gut microbiome has emerged as a critical modulator of cardiovascular disease (CVD) risk, offering a novel frontier for therapeutic intervention. This mini-review synthesizes current evidence on how probiotic-like bacteria and their metabolites mediate protective physiological mechanisms against CVD. Drawing from both animal models and human clinical trials, we elucidate the biological pathways, including trimethylamine-N-oxide (TMAO), short-chain fatty acids (SCFAs), and bile acid metabolism, through which the gut microbiota influences hypertension, atherosclerosis, and heart failure. Furthermore, we examine microbiota-based strategies such as dietary modification, fecal microbiota transplantation (FMT), and pharmacological agents aimed at restoring microbial homeostasis. Despite promising mechanistic insights, human trials have yet to consistently demonstrate significant clinical benefits in reversing CVD outcomes via gut microbiota modulation. This review underscores the necessity of moving from correlation to causation, highlighting current limitations and future prospects for leveraging gut microbiome research in the development of personalized, effective therapeutic strategies for cardiovascular diseases.